Thinking on Love: Harry G. Frankfurt’s Proposal - Aragón Aranda, Gabriel (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
This present paper suggests underlining the philosophical relevance of love, by turning to the analytical development conducted by Harry G. Frankfurt. In order to do this, we shall make use of the categorizations that Bennet Helm’s establishes and we shall classify Frankfurt’s Theory within a specific category: love as a «robust concern». This will help us attend to the moral psychology of the already stated author and the decisive role that love plays; covered with such authority, as Frankfurt states, that it gives ultimate meaning to our practical reasoning. Finally, and having set forth the relevance of love within all this process, we shall proceed to discuss alongside with Jonathan Lear if love has the authority that Frankfurt gives it.